2009
DOI: 10.1029/2008wr007063
|View full text |Cite
|
Sign up to set email alerts
|

Technological advances in suspended‐sediment surrogate monitoring

Abstract: [1] Surrogate technologies to continuously monitor suspended sediment show promise toward supplanting traditional data collection methods requiring routine collection and analysis of water samples. Commercially available instruments operating on bulk optic (turbidity), laser optic, pressure difference, and acoustic backscatter principles are evaluated based on cost, reliability, robustness, accuracy, sample volume, susceptibility to biological fouling, and suitable range of mass concentration and particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
172
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(175 citation statements)
references
References 59 publications
(74 reference statements)
1
172
0
2
Order By: Relevance
“…Diagnostic ultrasonic techniques however have proven to surmount such caveats to a practicable extent [1,30,31], enabling remote and relatively non-intrusive measurement with subsequently high resolution temporal and spatial profiles of suspended concentration, particle size and settling velocities [32]. Typical instrumentation include ex situ bench scale devices comprising separate transmitter and receiver probes [33][34][35], and even recent interest in B-scan ultrasound imaging [36].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic ultrasonic techniques however have proven to surmount such caveats to a practicable extent [1,30,31], enabling remote and relatively non-intrusive measurement with subsequently high resolution temporal and spatial profiles of suspended concentration, particle size and settling velocities [32]. Typical instrumentation include ex situ bench scale devices comprising separate transmitter and receiver probes [33][34][35], and even recent interest in B-scan ultrasound imaging [36].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the nonrandom variability in concentration about these curves, Glysson and others (2001), in an analysis of sediment data from 10 USGS gaging stations located in different regions of the United States, showed that the absolute value of the error in the annual sediment loads predicted by these curves fit to entire periods of record could equal 526 percent, and errors in the daily sediment loads predicted by sediment rating curves could be as high as 4,000 percent. Fortunately, the increasing availability of optical and acoustical sensors and associated advances in optical and acoustical theory have opened the possibility that these sensors may be used in conjunction with smaller numbers of conventional suspended-sediment samples to allow accurate sediment loads to be calculated (Gray and Gartner, 2009). Under conditions where suspended-sediment concentrations are not extremely high (that is, not >>1,000 mg/L), and concentration-independent changes in grain size or sediment color do not occur (for example, Conner and DeVisser, 1992;Sutherland and others, 2000;Voichick and Topping, 2014), measurements of optical-backscatterance (Schoellhamer, 2001;Schoellhamer and Wright, 2003) and turbidity (Rasmussen and others, 2009) have been shown to be highly correlated with conventional measurements of suspended-sediment concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential advantage of LASS is related to its relatively large sampling volume. The small measuring volume of turbidity probes and optical backscatter sensors enables these sensors to provide at-a-point surrogate measurement to TSS, which may not be representative of the mean cross-sectional TSS (Gray and Gartner 2009). The larger measuring volume of LASS provides a potential alternative and a more representative measurement for estimating suspended sediment flux.…”
Section: Discussionmentioning
confidence: 99%